PHYSICAL CAPITAL, HUMAN AND SOCIAL AND RESPONSIBILITY PUBLIC ACCOUNTANT WITH POVERTY - Wong Torres, Zelma (2011)
This article is the result of research carried out in 2010, entitled, physical capital, human and social, and social responsibility of the Certified Public Accountant with Poverty. This article seeks to demonstrate the interest in settlement mechanisms to achieve equity and achieve a development strategy. In this perspective, the article insisted that social policy should be able to influence the structural determinants through which reproduce poverty and inequality, maldistribution of educational and occupational opportunities, the sharp inequality the distribution of wealth, even high demographic dependency, and ethnic and gender dimensions that accompany them. From this analysis, we highlighted three factors as human capital, social and physical, while highlighting the role of social responsibility of the accounting profession.